Effect of Exogenous Salicylic Acid and Silicon Application on Salinity Tolerance of Rice - Rima, SA; Somaddar, U; Samanta, SC; Saha, G (Bangladesh Agronomy Journal, 2023)
Soil salinity remarkably hinders rice growth, development and productivity. The present study was set up to explore the role of exogenous salicylic acid (SA) and silicon (Si) application on the growth and yield performance of two contrasting rice genotypes, namely BRRI dhan41 (salt-tolerant) and BRRI dhan49 (salt-sensitive) under salinity. The experiment was laid out in a randomized complete block design with three replications and four SA and Si treatments such as control (tap water), 100 ppm SA, 100 ppm Si (as CaSiO3) and, co-application of SA and Si (50 ppm each). Results revealed that the maximum plant height (125.2 cm), fresh weight of shoot (267.3 g) and maximum K+/Na+ (5.2) were obtained in BRRI dhan49 after sole application of Si under salt stress. Besides, the number of grains per panicle and grains per hill significantly increased in BRRI dhan41 after the sole application of SA (64 and 46%, respectively) and co-application of SA and Si (29 and 21%, respectively), and in BRRI dhan49 with sole SA (182 and 277%, respectively) and Si (75 and 446%, respectively) compared with their respective controls. Besides, we observed that the K+/Na+ was increased where the shoot accumulation of Na+ reduced significantly in both rice varieties after sole and co-application of SA and Si compared with the untreated plants. However, the present findings showed new dimensions regarding the beneficial effects of Si on rice plants which could effectively be utilized to grow and maximize rice production in the saline-prone coastal areas of Bangladesh encountering detrimental effects of salt stress on rice. Bangladesh Agron. J. 2022, 25(2): 119-127